Dependence of the anisotropy parameter of drag thermal e.m.f. On the concentration of impurities in n-Ge and n-Si crystals - Gaidar, G.P.; Baranskii, P.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
At Т = 85 K, the concentration dependences of the anisotropy parameter of electron-phonon drag thermal e.m.f. in a wide range of concentrations (1,9 ⋅ 1012 ≤ne ≡ N1 ≤ 4,6 ⋅ 1017 cm−3) are investigated on n-Ge and n-Si crystals. It is shown that the parameter M is insensitive in n-Ge (unlike n-Si) to the presence of impurities in the crystals up to concentrations ∼1015 cm–3.